PERBANDINGAN REAKSI INVESTOR PADA INDUSTRI BERESIKO RENDAH DAN BERESIKO TINGGI SEBELUM DAN SELAMA MASA PANDEMI COVID-19 - Munifajri Dwi Nurmanto; Nur Diana; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The purpose of this study is to analyze the difference between Average Trading Volume Activity and Average abnormal return of stocks in low-risk industries and high-risk industries before and during the Covid-19 pandemic. The population in this study is manufacturing industry companies registered in Buersa Efek Indonesia (BEI) in 2019-2021. The samples in this study were 30 companies that were sampled in 2019 to 2021. The research methods used are data analysis methods, descriptive statistics, data normality tests using kolomogorov-smirnov tests as well as hypothesis tests using paired sample t-test. The results showed that in low-risk industries there is no difference in Average Trading Volume Activity and Average abnormal return and in high-risk industries there is a difference in Average Trading Volume Activity and Average abnormal return before and during the Covid-19 pandemic.Keywords : Low and High risk industries, Investor reactions, The Covid-19 pandemic